2016
DOI: 10.1183/13993003.00989-2015
|View full text |Cite|
|
Sign up to set email alerts
|

Tidal flow variability measured by impedance pneumography relates to childhood asthma risk

Abstract: Lung function variability is a fundamental feature of asthma but has been difficult to quantify in children due to methodological limitations. We assessed the feasibility and clinical implications of overnight flow variability measurement at home using impedance pneumography in young children.44 children aged 3-7 years with recurrent or persistent lower airway symptoms were recruited. Patients were divided into high- or lower-risk groups (HR and LR groups) based on their risk of asthma (modified Asthma Predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…However, for deriving complete TBFV curves by IP, high linearity with the flow signal is required. In preschool children, we have previously confirmed the validity of IP for recording tidal airflow profiles [13], and found that tidal breathing variability assessed by IP during home recordings is related to childhood asthma risk [14]. We have now found the linearity of IP to be comparable and therefore satisfactory to also study similar clinical correlates in infants.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…However, for deriving complete TBFV curves by IP, high linearity with the flow signal is required. In preschool children, we have previously confirmed the validity of IP for recording tidal airflow profiles [13], and found that tidal breathing variability assessed by IP during home recordings is related to childhood asthma risk [14]. We have now found the linearity of IP to be comparable and therefore satisfactory to also study similar clinical correlates in infants.…”
Section: Discussionmentioning
confidence: 52%
“…Recordings of longer duration also enable the calculation of more robust measures of tidal airflow profiles than the conventional TBFV parameters, as well as complex indices of flow variability [38]. By using nocturnal recordings with IP, we demonstrated that preschool children with a high risk of asthma present with an increased variation of tidal flow profile shape, and momentarily lowered chaoticity, compared to children with a lower risk of asthma [14]. Similar ambulatory applications could be envisioned for infants, but so far no data are available.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…TIP has been used to measure lung volume changes [255], to evaluate respiratory condition during normal and deep breathing [256], the assessment of asthma risk from tidal flow variability [257], sleep disorders [258], energy expenditure estimation [259], or even the detection of body posture changes [260]. Another application of TIP is the gating of positron-emission tomography (PET) and singlephoton emission computed tomography (SPECT) images.…”
Section: Transthoracic Impedance Pneumographymentioning
confidence: 99%
“…Therefore, tidal breathing flow volume measurements have been used instead to characterise lung functions in infants and young children . A number of techniques have been developed that estimate tidal breathing from chest movements, such as respiratory inductive plethysmography , optoelectronic plethysmography or impedance pneumography . These techniques can provide useful information related to ventilatory effort or estimate changes in lung volumes.…”
Section: Introductionmentioning
confidence: 99%